Soil fertility and bacterial community composition in a semiarid Mediterranean agricultural soil under long‐term tillage management. (22nd September 2020) - Yaghoubi Khanghahi, Mohammad; Cucci, Giovanna; Lacolla, Giovanni; Lanzellotti, Loredana; Crecchio, Carmine
Abstract: This research attempted to investigate a part of the United Nations sustainable development goal 15, dealing with preventing land degradation and halting the loss of microorganisms' diversity. Since soil deterioration and biodiversity loss in the Mediterranean area are occurring because of intensive management, we evaluated some biochemical and microbiological parameters and bacterial biodiversity under long‐term conventional tillage (CT) and no‐tillage (NT) practices, in Basilicata, a typical Region of Southern Italy, characterized by a semiarid ecosystem. The highest biological fertility index (BFI) (composed of soil organic matter, microbial biomass C, cumulative microbial respiration during 25 days of incubation, basal respiration, metabolic quotient and mineralization quotient) was determined for the 0–20 cm of NT soil (class V, high biological fertility level). The analysis of the taxonomic composition at the phylum level revealed the higher relative abundance of copiotrophic bacteria such as Proteobacteria, Actinobacteria and Bacteroidetes in the NT soil samples as compared to the CT soil. These copiotrophic phyla, more important decomposers of soil organic matter (SOM) than oligotrophic phyla, are responsible of a higher microbial C use efficiency (CUE) in tilled soil, being microbial community composition, C substrates content and CUE closely linked. The higher Chao1 and Shannon indices, under the NT management, also supported the hypothesis that the bacterial diversity and richness increased in the no‐till soils. In conclusion, we can assume that the long‐term no‐tillage can preserve an agricultural soil in a semiarid ecosystem, enhancing soil biological fertility level and bacterial diversity.